The role of human resources in the innovative development of oil companies. (Journal of Economic Research & Business Administration, 2015)
Dynamic development of any enterprise demands the corresponding staffing. Now a day the strategic problems of a state policy demanding the prime solution for creation innovative model of national economy is personnel capacity development of the country by a creation of effective system professional competences formation of enterprise staff necessary for implementation of innovative activity. Formation and broad use of professional competences of this type will promote implementation of the accelerated modernization of the domestic industry on the basis of the knowledgeintensive productions creation which are carrying out release of competitive production. The oil companies develop and start realizing programs of the innovative development which achievement of the objectives is impossible without formation of professional competences of the personnel on management of innovative activity as the most important component of the intellectual capital of the modern enterprise. Thus processes of formation of these competences have to cover all professional groups of employees at various levels functioning of the companies.
Keywords: Personnel potential; innovative development; oil companies; innovative and technological policy